The gait, arms, legs and spine (GALS) locomotor screen teaching-learning package Has it achieved its intended learning outcome? - Tee, Michael L.
Musculoskeletal conditions are the leading causes of disability worldwide. However, clinicians rarely screen their patients for musculoskeletal disorders. Reasons are varied. It has been noted that teaching of musculoskeletal medicine is not adequate. Unfortunately, if this trend continues, patients with locomotor complaints will receive suboptimal treatment. To address the issue, international groups defined a common core curriculum that will serve as a guide in developing undergraduate courses in musculoskeletal system. In the UP College of Medicine, the Section of Rheumatology (Rheuma) adopted the use of the Gait, Arms, Legs and Spine (GALS) locomotor screen as a central focus of instructions on musculoskeletal condition. The students are evaluated using an objective structured clinical examination (OSCE) at the end of their course. Objectives: The aims of this study were to determine the extent of medical interns' routine musculoskeletal assessment amongst medical out-patients and to determine the effects that GALS teaching-learning package during their Year Level VI physical diagnosis class has on this. Methods: General medical out-patient charts were reviewed. Medical interns were asked to answer a questionnaire. They were also interviewed to determine their confidence in performing musculoskeletal screening and whether they routinely do so. Those who do were asked whether they use the GALS technique. The students were also asked which among the four teaching-learning strategies used by Rheuma is deemed most effective in ensuring the achievement of the intended learning outcomes. Lastly, the students were interviewed as groups to explore their views regarding musculoskeletal problems and how it can be best taught to students. Results: The students expressed confidence they can perform musculoskeletal screening examination. However, only 26% claimed they routinely do, while only 21% claimed they use the GALS screen in doing so. The presence of locomotor symptoms was recorded in 42.51%, while signs were recorded in 39.52% of the charts reviewed. Teaching of the GALS screen using demonstration-return demonstration received the highest approval rating among students. Finally, the students enumerated barrier to the routine application of GALS screen in the clinics. Conclusions: While students are competent to perform GALS screen among their patients, its application leaves much to be desired. Consistency of educational focus in related subspecialties would go a long way in delivering a common message on the importance of performing a routine musculoskeletal examination among medical students.